Atlas of african agriculture research and development [Preview]: Revealing agriculture's place in Africa - International Food Policy Research Institute; Wood, Stanley; Wood-Sichra, Ulrike; Koo, Jawoo; Sebastian, Kate; Beintema, Nienke M.; Thornton, Philip K.; Guo, Zhe; Azzarri, Carlo (International Food Policy Research Institute, 2013)
This preview of the Atlas of African Agriculture Research and Development is an introduction to a multidimensional resource that will highlight the ubiquitous role and importance of smallholder agriculture in Africa; the multitude of factors shaping the location, nature, and performance of agriculture enterprises; and the strong interdependencies among farming, natural resource stocks and flows, and the well-being of the poor.